PRESENTASI DIRI “AYAM KAMPUS” (STUDI DRAMATURGI MENGENAI PERILAKU MENYIMPANG MAHASISWI DI PEKANBARU) - QURRATA AINI; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The female collage student as “Ayam Kampus” its not only an issue but there really is. They always give an impressive performace’s attitude beyond her mask. The objective of this research was to determine how is the front stage and back stage behind a “Ayam Kampus” among female college students in the city of Pekanbaru and to learn how a self presentation of “Ayam Kampus” among female college students.The type of research was descriptive qualitative, by an approach of dramaturgy. Based on the fact, the field through observation, interviews and documentation. The subject of research was a female college student with a profession as hostess or “Ayam Kampus”. Informants in this research consists of 3 peoples. Data analysis technique used is to use interactive analysis model using data validity checking techniques and triangulation.The finding of research showed that the front stage of a “Ayam kampus” could adapt to the norms and values prevailing in society through the role they play as a student is seen from the physical appereance, attitude and behavior on campus and other social environments. While in the back stage where the environmets is more narrow scope with the values and norms that are very loose enabling them to meet the needs of economy, sexs, and the existence of self as a glaamor and modern’s women in a way become sex workers. And on the back stage, the informants showed another side of her taht is not bound to the rules of the front stage but undergro the rules and norms of back stage are made unanimously in their favor of course. Self-presentation as a a student informant and beyond “Ayam Kampus” shows the results where the difference of each informant in managing roles and impression you want displayed and perceived by them while in front stage and back stage.Keyword: self-presentation, ayam kampus, dramaturgy, behavior